Поняття гібридності в сучасному україномовному інформаційному просторі: мовознавчий аспект - Мірончук, Тетяна А.; Одарчук, Наталія Андріївна; Mironchuk, Tetiana A.; Odarchuk, Nataliia A. (Scientific Educational Center Warsaw, 2019)
The paper addresses the notions of hybridity («гібридність») and discusses social preconditions that account for its recurrence in the Ukrainian culture. The issue is explored via social, political, scientific, and cultural spheres, which make lingual context for the external semantics of the notion of hybridity. The internal semantics of the notion is studied through its dictionary definitions. As a result, there are revealed denotative and connotative semes that are indicative of and associated with the notion “hybridity” in the Ukrainian culture.
Keywords: hybridity; semes analysis; definition analysis; semantic field differentiation; connotative semes; denotative semes; identity; valorative semantics